Gastrointestinal side effect profile due to the use of alendronate in the treatment of osteoporosis - AKYÜZ, GÜLSEREN DERYA (YONSEI UNIV COLL MEDICINE, 2003)
The aim of our study was to evaluate the upper gastrointestinal (GI) tract side effect profile in 759 female patients that had taken alendronate (10 mg/day), for at least 6 months, for the treatment of osteoporosis, in relation to the safety of alendronate and the compliance of patients to its absorption rules. This study was a multicentered retrospective, clinical, non-placebo controlled, study of 759 female subjects carried out at 26 centres in 6 different regions of Turkey. The mean age of our patients was 62.6 +/- 8.6, with 51.2% in the age range 60 to 69 years. 158 patients (20.8%) were considered to have upper GI tract complaints with nausea as the most often encountered symptom. Of the subjects with upper GI tract complaints, 20% reported discontinued drug use, and 30% reported the requirement of an additional drug in order to abolish their complaints. Approximately 537 (71%) of the patients stated they had been given written information about the administration of the drug, and at least 93 patients (12%) and 73 patients (18.4%) acknowledged non compliance with the safety and absorption rules, respectively. In our study, no significant difference was found between the adherence to the safety measures and upper GI tract complaints (p>0.05), but that upper GI tract complaints were higher in patients taking additional medication to alendronate (p<0.05).
Keywords: osteoporosis; alendronate; gastrointestinal system; side effect profile; FRACTURE-INTERVENTION-TRIAL; BONE MASS; POSTMENOPAUSAL WOMEN; VERTEBRAL FRACTURES; RANDOMIZED-TRIAL; ORAL ALENDRONATE; DENSITY; RISK; MECHANISMS; SYMPTOMS